The art of client service : the classic guide - Solomon, Robert, 4 0 16; 5 (Hoboken, NJ : Wiley, 2016)
A practical guide for providing exceptional client service Most advertising and marketing people would claim great client service is an elusive, ephemeral pursuit, not easily characterized by a precise skill set or inventory of responsibilities; this book and its author argue otherwise, claiming there are definable, actionable methods to the role, and provide guidance designed to achieve more effective work. Written by one of the industry's most knowledgeable client services executives, the book begins with a definition, then follows a path from an initial new business win to beginning, building, losing, then regaining trust with clients. It is a powerful source of counsel for those new to the business, for industry veterans who want to refresh or validate what they know, and for anyone in the middle of the journey to get better at what they do--;In a letter to the author, advertising agency Ogilvy & Mather's Chair and CEO emeritus Shelly Lazarus said, The book is terrific. It's an easy read, and I agree with every word. Danny Meyer, legendary restaurateur and CEO of the Union Square Hospitality Group, described the book as providing, sensible, timeless advice for distinguishing your brand through generosity of spirit. This book outlines how to build better client relationships and work smarter with colleagues. It transforms what is viewed as an elusive, even ephemeral pursuit, not easily characterized by a precise skill set or inventory of responsibilities, into something definable and actionable, governed by a precise checklist of things designed to help guide work. The new version begins with a synthesis discussions the author has had with a wide range of advertising and marketing people about what's wrong with advertising, setting up the material to follow. It ends with a provocative question, Is account management dead, that the author counters in convincing fashion. In between there is practical, accessible content designed to help people get better at what they do--
Machine generated contents note: Dedication Foreword Introduction 1. What Makes Great Client Service? PART ONE: HOW TO BE GREAT WITH CLIENTS 2. Account Management's Role 3. Achieving The Next Level 4. Transforming A Career Into A Calling PART TWO: WINNING NEW BUSINESS FOR YOUR AGENCY 5. New Business: What It Is, Why It Is Important, And Why You Should Give A Damn 6. How To Contribute Before, During, And After Pitch Day 7. Getting To Yes PART THREE: BEGINNINNG A CLIENT RELATIONSHIP 8. In A High-Tech World, Be Low-Tech 9. What Success Looks Like 10. Always Manage Client Expectations From The Outset 11. Be Multilingual 12. Live The Client's Brand 13. Ask, What Do My Colleagues Need To Create Great Advertising? Then Deliver It PART FOUR: HOW TO
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; Advertising.;Marketing.;Customer relations. -- 20; 20; Electronic books. -- 2